α-Synuclein Inhibits Intersynaptic Vesicle Mobility and Maintains Recycling-Pool Homeostasis - Scott, David (Society for Neuroscience, 2012)
Although the presynaptic protein α-synuclein is a recognized player in neurodegeneration, its precise physiologic function(s) and/or role in human disease remains unclear. An emerging consensus from previous studies in lower-order systems is that α-synuclein interferes with vesicle-trafficking pathways; however putative neuronal correlates are unknown. Here we explore consequences of α-synuclein modulation in cultured mouse hippocampal neurons; coupling α-synuclein overexpression and knock-out model-systems with contemporary imaging paradigms. Our studies reveal an unexpected role of α-synuclein in attenuating the mobility of recycling pool (RP) vesicles between presynaptic boutons—called “superpool” trafficking—and also in maintaining the overall size of RPs at synapses. While an excess of α-synuclein led to smaller RPs and inhibited intersynaptic trafficking, an absence of α-synuclein triggered converse changes with larger RPs and enhanced intersynaptic trafficking. The data collectively suggest a model where α-synuclein maintains RP homeostasis by modulating intersynaptic vesicular dynamics, and provide a putative neuronal correlate of α-synuclein-induced impairments in vesicle-trafficking previously reported in lower-order systems.